2014
DOI: 10.4251/wjgo.v6.i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant fluoxetine and its potential against colon tumors

Abstract: Colon cancer is one of the most common tumors worldwide, with increasing incidence in developing countries. Patients treated with fluoxetine (FLX) have a reduced incidence of colon cancer, although there still remains great controversy about the nature of its effects. Here we explore the latest achievements related to FLX treatment and colon cancer. Moreover, we discuss new ideas about the mechanisms of the effects of FLX treatment in colon cancer. This leads to the hypothesis of FLX arresting colon tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 97 publications
(177 reference statements)
1
13
0
Order By: Relevance
“…Instead, fluoxetine itself caused a slight G1 arrest along with a marked induction of p27 as well as slight reduction of cyclin D1 and p53. Our results were similar to previous studies related to the effect of fluoxetine on G1 arrest and upregulations of p27 in human cervical cancer cells (SiHa), breast cancer cells (MDA-MB-231) and colon cancer cells HT29 (28)(29)(30). In addition, the dosage of fluoxetine as a chemosensitizer is kept under the range of 5-20 µM, where this agent itself does not affect cell viability (15).…”
Section: Discussionsupporting
confidence: 75%
“…Instead, fluoxetine itself caused a slight G1 arrest along with a marked induction of p27 as well as slight reduction of cyclin D1 and p53. Our results were similar to previous studies related to the effect of fluoxetine on G1 arrest and upregulations of p27 in human cervical cancer cells (SiHa), breast cancer cells (MDA-MB-231) and colon cancer cells HT29 (28)(29)(30). In addition, the dosage of fluoxetine as a chemosensitizer is kept under the range of 5-20 µM, where this agent itself does not affect cell viability (15).…”
Section: Discussionsupporting
confidence: 75%
“…In some clinical studies, a 50% reduction of risk of colon cancer was reported in patients treated with fluoxetine (Coogan et al, 2009). Various animal studies also supported a reduction in colon cancer incidence and many different signalling pathways such as NF-κB, ROS formation and cell cycle arrest were reported as the likely mechanisms of action in a variety of different carcinoma cells (Koh et al, 2011;Tutton & Barkla, 1986;Kannen et al, 2011Kannen et al, , 2012Lee et al, 2010, Krishnan et al, 2008Stopper et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, paroxetine induces cell apoptosis through MET and ERBB3 inhibition, leading to the induction of the JNK and caspase-3 pathways and the reduction of the expression of antiapoptotic protein Bcl-2 [ 62 , 63 ]. On the other hand, fluoxetine showed an antiproliferative effect on colon cancer cells by the reduction of VEGF expression [ 64 ] and by the alteration of tumour-related energy generation machinery [ 65 ], especially under conditions of hypoxia. Recently, Marcinkute et al confirmed fluoxetine’s cytotoxicity in human colon cancer cells through p53-independent apoptosis [ 66 ].…”
Section: Resultsmentioning
confidence: 99%